(untitled) (Journal of Health, Population and Nutrition, 2013)
The aim of this study is to compare accessibility of vision-impaired (VI) patients to other eyecare centres before attending the mobile and stationary hospitals. Under a cross-sectional study design, VI patients were consecutively enrolled if they visited one of the three Impact Foundation Hospitalsone mobile and two stationary hospitals. The cost and service output of all hospitals were also reviewed; 27.7% of patients at the mobile and 36.8% at the two stationary hospitals had sought eyecare at other health facilities in the past. Mobile hospital patients lived closer to the hospital but spent more time in travelling, bore less direct cost, needed less extra support, and had a higher level of satisfaction on the service. They also identified more barriers to access eyecare in the past. The mobile hospital had a higher percentage of patients with accessibility problems and should continue to help the remote population in overcoming these problems. J HEALTH POPUL NUTR 2013 Jun; 31(2): 223-230 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16387